Model Integrasi Triadik dalam Implementasi Strategi: Kepemimpinan Berbasis Tafahum Strategis di SMP Islam: Triadic Integration Model for Strategic Implementation: Tafahum Strategis-Based Leadership in Islamic Junior High Schools - Ayi M Sirojudin; Mulyawan Safwandy Nugraha; Komarudin (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2026)
This study addresses the persistent challenges of strategic implementation in Islamic educational institutions, where the integration of Islamic values into management practices often remains symbolic and unstructured. It aims to analyze the role of leadership in strategy implementation at SMP Al-Azhar Syifa Budi Parahyangan, to describe the application of the Tafahum Strategis framework, to identify supporting and hindering factors, and to formulate a triadic integration model. A qualitative case study approach was employed, utilizing in-depth interviews, participant observation, document analysis, and NVivo 12 for data analysis, with triangulation and member checking ensuring trustworthiness. The findings reveal that leadership functions as a strategic driver that translates vision into operational programs through the four stages of Tafahum Strategis: Tafakkur (reflection), Tawashau (consultation), Tanfidz (execution), and Muhasabah (evaluation). Supporting factors include high vision acceptance, a collaborative culture, and data-driven monitoring, while resistance, resource limitations, and external dynamics pose challenges. The triadic integration model combining Islamic values, strategic theory, and operational practice proves effective in enhancing consistency and institutional performance. The study concludes that leadership grounded in Tafahum Strategis significantly improves strategy implementation in Islamic education and offers a cross-religious model adaptable to other faith‑based institutions.